2009
DOI: 10.1002/mds.22460
|View full text |Cite
|
Sign up to set email alerts
|

Association of restless legs syndrome with nocturnal eating: A case‐control study

Abstract: Abstract:We investigated the prevalence of nocturnal eating (sleep-related eating disorder-SRED or night-eating syndrome-NES) in patients with restless legs syndrome (RLS). One hundred RLS patients living in Emilia-Romagna (Northern Italy) and 100 matched controls randomly selected from the general population received two telephone interviews, and were investigated for socio-demographic characteristics, general health status, and presence of nocturnal eating. Additionally, subjects underwent interviews for psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 17 publications
3
66
0
2
Order By: Relevance
“…Thus, the actual prevalence of the RLS clinical spectrum is likely larger than current estimates. These findings bear special significance for the obesity pandemic since according to this study and others, 4 the majority of RLS patients have NE, and more than a third have SRED. …”
Section: Epidemiology Of Ne/sred and Rlssupporting
confidence: 73%
See 4 more Smart Citations
“…Thus, the actual prevalence of the RLS clinical spectrum is likely larger than current estimates. These findings bear special significance for the obesity pandemic since according to this study and others, 4 the majority of RLS patients have NE, and more than a third have SRED. …”
Section: Epidemiology Of Ne/sred and Rlssupporting
confidence: 73%
“…In fact, subjects whose nocturnal eating symptoms were under control were more likely to be on these agents than subjects who continued to have nocturnal eating. 4 Further, a double-blind treatment trial of pramipexole for SRED demonstrated improved sleep and reduced nighttime activity, although, admittedly, nocturnal eating ingestions were not reduced in this small study. 34 In the series published here, we monitored therapy outcome in 44 RLS patients previously unexposed to dopaminergics with and without NE.…”
Section: Ne/sred In Rls Is Relieved By and Not Caused By Dopaminergicmentioning
confidence: 58%
See 3 more Smart Citations